Retinal vessels caliber assessment in patients with arterial hypertension - N. S. Semenova; V. S. Akopyan; I. V. Filonenko (Oftalʹmologiâ, 2014)
Purpose: to evaluate the diagnostic capability of automated retinal vessels (RV) caliber estimation for hypertensive angiopathy.Methods: this study included 146 patients (292 eyes) with arterial hypertension. All the subjects underwent fundus photography and RV caliber estimation. the latter was performed using newly developed computer-based method for automated vessel detection and central retinal arteriolar and venular equivalents determination (CRAE & CRVE). Sensitivity, specificity, and reproducibility of the method were estimated.Results: the method of RV caliber assessment showed good reproducibility. the overall specificity and sensitivity were 74% and 80.77%, respectively. Computer-based method of retinal vascular caliber assessment revealed higher predictive value comparing with ophthalmoscopic assessment (AUC = 0.903 and 0.85, respectively). Retinal arteriolar and venular caliber and AVR tend to decrease with age. Higher blood pressure is associated with narrower retinal arterioles.Conclusion: Novel method of RV caliber estimation demonstrated high information value. these findings are in good agreementwith data from major population-based studies.